Selection, evolution and persistence of paleoecological systems - Roopnarine, Peter D. (Frontiers in Earth Science, 2025)
The Phanerozoic fossil record can be organized as a nested set of persistent paleoecological units, ranging from paleocommunities to Sepkoski’s Evolutionary Faunas. This paper argues that the basis for ecological persistence on geological timescales is rooted in the robustness of ecological communities, that is, the resistance and resilience of communities when perturbed by the environment. Here I present the Ecological Functional Networks Hypothesis (EFNH) that proposes that networks of species functions, or Ecological Functional Networks (EFNs), underlie ecological stasis and persistence, and that EFNs are both subject to selection and evolve. An EFN varies if the species composition and hence functional structures of its constituent communities vary, and EFNs may differ from each other based on the robustness of those constituent communities, numerical representation, and biogeographic distribution. That variation is subject to selection acting on EFN community composition, and determines both the persistence of an EFN and the differential persistence among multiple EFNs. Selection pressures on EFNs in turn exert top-down influence on species evolution and extinction. Evidence is presented to both establish the reality of EFNs in the fossil record, for example, community structures that persist even as species composition changes, and the selection of EFNs, which is apparent during and after episodes of severe biotic turnover such as mass extinctions. Finally, tests are suggested that make the EFNH falsifiable, including testing the correlation between EFNs or EFN emergent traits and geological persistence, and using models of paleocommunity dynamics to examine the relationship between community or EFN robustness and geological persistence. The tests should be applied broadly throughout the Phanerozoic and diverse environments. The EFNH is part of a growing body of hypotheses that address the selection, evolution and persistence of non-reproducing systems, including ecosystems and entire biospheres, and addresses those concepts on geological timescales.